2000
DOI: 10.1520/jfs14773j
|View full text |Cite
|
Sign up to set email alerts
|

Improved Method for Shooting Distance Estimation. Part 1. Bullet Holes in Clothing Items

Abstract: An improved method for firing distance estimation on clothing is described. The novel part of the method includes transfer of total nitrite (nitrite ions and smokeless powder residues) from the target to an adhesive lifter. After the transfer, lead and copper deposits around the bullet entrance hole are visualized by rhodizonate and rubeanic acid, respectively. The Modified Greiss Test is carried out after alkaline hydrolysis of the smokeless powder residues on the adhesive lifter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 7 publications
0
54
0
3
Order By: Relevance
“…However, in the literature on chemical safety data [67], N-(1-naphthyl)ethylenediamine dihydrochloride is not reported as being carcinogenic. In fact, in Israel this reagent is used with sulfanilamide routinely for "the local" MGT [68]. The term MGT does not refer to one specific defined test, in fact it seems that every author who introduces any modification to the original Griess test calls it an MGT.…”
Section: Visual/microscopic and Color Testsmentioning
confidence: 99%
“…However, in the literature on chemical safety data [67], N-(1-naphthyl)ethylenediamine dihydrochloride is not reported as being carcinogenic. In fact, in Israel this reagent is used with sulfanilamide routinely for "the local" MGT [68]. The term MGT does not refer to one specific defined test, in fact it seems that every author who introduces any modification to the original Griess test calls it an MGT.…”
Section: Visual/microscopic and Color Testsmentioning
confidence: 99%
“…However, in the literature on the chemical safety data [10], N-(1-naphthyl)-ethylenediamine dihydrochloride is not reported as a carcinogen. In fact, we are using this reagent with sulphanilamide routinely for "our" MGT [11,12,13,14]. MGT does not refer to one specific, defined test.…”
Section: Clothing Targetsmentioning
confidence: 99%
“…Glattstein et al reported on an improved method of determining shooting distance estimation from clothing [12]. The novel part of the method includes transferring total nitrite (nitrite ions and unburned smokeless powder residues) from the target to an adhesive lifter.…”
Section: Clothing Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the matter of reconstruction of gunshot fatalities, the macroscopic examination of gunshot wounds as well as the investigation of GSR particles gains extensive forensic signifi cance (1,2). Physical and chemical investigations of fi rearm discharge residues are nowadays performed routinely in order to solve a number of forensic problems such as identifi cation of gunshot wounds together with establishing of the entrance and exit (3), estimation of the time since discharge of a fi rearm (4,5), distribution of GSR at the crime scene, estimation of shooting distance (6,7), as well as establishing whether a person has fi red a gun (8). Sensitive analytical methods are required for the identifi cation of inorganic gunshot residues that are usually presented in very small quantities on a substratum, and commonly used methods include atomic absorption spectroscopy (AAS), neutron activating analysis (NAA) (1) , X-ray fl uorescence spectrometry (XRF), inductively coupled plasma mass spectrometry (ICP-MS) (9).…”
Section: Introductionmentioning
confidence: 99%